Produção do gênero notícia: desenvolvimento de capacidades de linguagem em situação de ensino-aprendizagem - De Lucci, Aline Grazielli [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The aim of this study was to develop the language abilities of the learners in a context of teaching-learning in the discipline of Portuguese Language of a 6th grade students, having as articulating instrument of social practices and practices of language in the classroom the textual genre news. For this, this research used the transposition and didactic modeling of this genre on the theoretical-methodological references of Sociodiscursive Interactionism (SDI) (BRONCKART, 2012) and the Didactics of the Geneva group (SCHNEUWLY; DOLZ, 2004). This research shows the development of a Didactic Sequence (DS) from the textual genre news in order to achieve the general objective, as well as the analysis and learning outcomes resulting from the development of this DS performed with a group of the 6th year of Teaching. It is fundamental, based on the conception that students mobilize three language capacities (of action, discursive and linguistic-discursive) in the process of textual production (SCHNEUWLY; DOLZ, 2004). DS was developed in order to provide students with the mobilization of their capacities and develop others of students developmental zone. The methodology used resulted in a DS composed of nine workshops distributed in four stages. The results were obtained from the analysis with an evaluative-comparative approach of the initial and final productions of the news genre based on proposal analysis of text suggested by Bronckart (2012), supported by language capabilities that support this research in order to verify if there was an expansion of the language abilities of students according to didactic procedures achieved.

A presente pesquisa teve como objetivo geral desenvolver as capacidades de linguagem de uma turma do 6º ano do Ensino Fundamental II em contexto de ensinoaprendizagem, na disciplina de Língua Portuguesa, tendo como instrumento articulador entre as práticas sociais e práticas de linguagem na sala de aula o gênero notícia. Para isso, esta pesquisa utilizou a transposição e modelização didática desse gênero fundamentada nos referenciais teórico-metodológicos do Interacionismo Sociodiscursivo (ISD) (BRONCKART, 2012) e da Didática do grupo de Genebra (SCHNEUWLY; DOLZ, 2004). Esta pesquisa apresenta o desenvolvimento de uma Sequência Didática (SD) a partir do gênero textual notícia com a finalidade de atingir o objetivo geral, assim como a análise e os resultados de aprendizagem decorrentes do desenvolvimento dessa SD, fundamentados na concepção de que os alunos mobilizam três capacidades de linguagem (de ação, discursiva e linguístico-discursiva) no processo da produção textual (SCHNEUWLY; DOLZ, 2004). A SD foi desenvolvida a fim de proporcionar aos alunos a mobilização das capacidades já adquiridas e desenvolver outras da zona de desenvolvimento proximal dos aprendizes. A metodologia utilizada resultou em uma SD composta por nove oficinas distribuídas em quatro etapas. Os resultados foram obtidos a partir da análise com enfoque avaliativocomparativo das produções iniciais e finais do gênero notícia, tendo como base a proposta de análise do texto postulada por Bronckart (2012), a fim de validar a ampliação das capacidades de linguagem dos aprendizes em decorrência dos procedimentos didáticos realizados.
Keywords: Didática; Língua portuguesa; Aprendizagem; Ensino fundamental; Teaching